A Fundamental Asymmetry in Human Memory: Old [not equal to] Not-New and New [not equal to] Not-Old - Brainerd, C. J; Bialer, D. M; Chang, M; Upadhyay, P (Journal of experimental psychology. Learning, memory, and cognition, 2022)
In recognition memory, anything that is objectively new is necessarily not-old, and anything that is objectively old is necessarily not-new. Therefore, judging whether a test item is new is logically equivalent to judging whether it is old, and conversely. Nevertheless, a series of 10 experiments showed that old? and new? judgments did not produce equivalent recognition accuracy. In Experiments 1-4, wherein subjects made old? or new? judgments about test items, new? judgments yielded more accurate performance for old items than old? judgments did, and old? judgments yielded more accurate performance for new items than new? judgments did. This same violation of logical equivalence was observed in Experiments 5-10, wherein subjects made similar? judgments as well as old? and new? ones. In short, old? and new? judgments displayed consistent Judgment × Item crossovers, rather than equivalence. Response latencies were used to test the hypothesis that Judgment × Item crossovers were due to certain judgment-item combinations provoking more deliberate, thorough retrieval than other combinations. There was no support for that hypothesis, but the data were consistent with an earlier theory, which posits that latency depends on the extent to which judgments or items slant retrieval toward accessing verbatim traces.